Effect of raised potassium on ventilation in euoxia, hypoxia and hyperoxia at rest and during light exercise in man. - Qayyum, MS; Barlow, C; O'Connor, D; Paterson, D; Robbins, P (1994)
The purpose of this study was to determine whether changes in arterial plasma potassium concentration [K+]a affect expired ventilation (VE) in euoxia, hypoxia and hyperoxia during rest and light exercise in humans. Three periods of ventilatory measurements were undertaken in eight healthy subjects at rest and in seven other subjects during cycle ergometry (70 W). The first period of measurement was before the ingestion of 64 mmol of potassium chloride (KCl), the second 20 min after ingestion of KCl when [K+]a levels were elevated, and the third 3 h after the ingestion of KCl when [K+]a had returned substantially to normal. During each period, end-tidal PO2 was cycled between euoxia, hypoxia and hyperoxia, whilst the end-tidal PCO2 was maintained constant. The acute ventilatory response to hypoxia (AHVR) was calculated as the difference in VE during hypoxia and hyperoxia within each period of measurement. Oral KCl produced a 1.3 +/- 0.2 mM (mean +/- S.E.M.) increase in [K+]a at rest and a 0.8 +/- 0.2 mM increase during exercise. There was no significant difference in ventilation during euoxia between the three periods of measurement at rest or during exercise. There was a significant increase in AHVR with the rise in [K+]a of 21 min-1 mM-1 at rest (arterial PO2 during hypoxia ca 57 Torr) and 10 l min-1 mM-1 during exercise (arterial PO2 during hypoxia ca 52 Torr). There was a significant difference in the absolute increase in AHVR with [K+]a between rest and exercise, but this difference was not significant if the increase in AHVR with [K+]a was expressed as a percentage of the initial AHVR. We conclude that changes in [K+]a of the order of 1 mM have little effect on euoxic ventilation at rest or during light exercise in humans. We also conclude that [K+]a changes of this order increase AHVR at rest and during light exercise and that increases in [K+]a contribute to the increase in AHVR with exercise in humans.